(3HdhZ GdCefjI aj EfeG GdCYeGd HGdfjIs - (3GdeQMhej, CMeO Hf eMeO Hf CHj GdNjQ, cGf MjG (B1075 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CjO YHGOg HfUQg CeG HYO aEf SHH JMHjQ gPg GdhQbGJ ajeG jJYdb Hbhdg Udi Gddg Ydjg hSde (B" (3EfeG GdCYeGd HGdfjGJ (B" (3gh Gf MVQI ehdGfG GdhRjQ MeRI HGTG hSejJgG HdhZ GdCefjI aj EfeG GdCYeGd HGdfjI s
(3BNQgG (B:s
(3hGdNQhL ef Jdc GdegGdc dJONd aj bhdg dG JRGd WGFaI ef CeJj XGgQjf Ydi GdMb MJi jCJj CeQ Gddg hge Ydi Pdc hjcajc gPg GdYhGFO GdSfjI hGdahGFO GdSfjI aj HjGf bhdg Udi Gddg Ydjg hSde (B" (3EfeG GdCYeGd HGdfjI (B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1 / 263s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdMOjK hGdeUWdMs